Interrogating travel : guidance from a reluctant tourist - Lindholdt, Paul J. (Louisiana State University Press, 2023)
"Interrogating Travel fuses firsthand narratives with research about the travel trade, telling the story of the author's reluctant world travel while arguing that carbon-intensive trips abroad may be offset if travelers come to know and love the landscapes closer to home. The initial manuscript was nearly complete when the COVID pandemic hit, and the final chapter, "Tidings from the Virus," contrasts viral shocks to the tourist industry with the lockdown's manifold advantages for nature. In the book's first section, "Among the Beloved," Lindholdt relates the disappearance of a son who was kayaking in Puget Sound, a painful story that frames the rest of the section (and the book as a whole) with the reminder of the importance of spending time with loved ones and doing what one loves. "Among the Predatory," the book's second section, looks closely at predation as it inflects travel's larger trends. Connections are made between "natural" predation and some astonishingly voracious human activities. "Shooters and the Tools They Use" analyzes the sport of hunting to show humankind's aptitude for rapacity. Our power plants and cars, our airplanes and factories, are symptomatic figuratively of our predatory habits. This section begins with a belated honeymoon in Paris, France, and it concludes with backyard observations of a wild hawk. Birdwatching as a counterpart to travel necessitates no internal combustion. Finally, "Among the Indigenous" takes readers to destinations near and far to contemplate the impacts of first-world business and industry upon natives of Hawaii, Belize, French Polynesia, Thailand, and the Pacific Northwest. For all the lip service paid to preserving traditional cultures, the tourist trade often dictates their degeneration. Most of the Indigenous folks who appear in this section are micro-minorities, their populations shrinking before the onslaught. Tourism, according to the World Trade Organization, may be the planet's largest industry. The present book conducts readers to local getaways and to some of the planet's most remote locations, all while urging mindfulness of unforeseeable outcomes"--